A retrospective study on pre-eclampsia in Hospital Universiti sains Malaysia, Kelantan - Mahamooth, Mas Irfan Jaya (2018)
To determine the prevalence, sociodemographic and characteristics of patients with pre-eclampsia attending HUSM and subsequently determine the maternal and perinatal outcomes. of these patients. Methodology: Descriptive study, retrospective data collection for 10 years duration from 2006-2016. Material and method: 283 cases were selected randomly and all important data such patients age, parity, BMI, medical background, gestation, clinical complaints, relevant laboratory results, mode of delivery, maternal and fetal complications were recorded and analysed. Results: The prevalence of pre-eclampsia in HUSM for that period of study was 1.4 percent. Mean age of the patients were 30.39 years. Majority (98.2%) of patients with pre-eclampsia had antenatal booking, 59% were multigravida, while 41% were primigravida . Our patients had a mean BMI of 30 kg/m2 and a mean haemoglobin of 10.2 g/dl . 64.7% has a raised serum uric acid level, 94% had a raised ALT level and 53% had a raised AST level. 23% of patients suffered from complications, with the most common being PPH (9.5%). A platelet level of <150 x109 was associated with a significant risk of maternal complications (95% CI 1.57, 6.52, p=0.001). Mean fetal weight was 2.53 kg, and 37% needed NICU admission. Patients with GDM had significantly higher odds of having low birth weight fetus (95% CI 2.38, 8.69, p<0.001) and more likely to be admitted to NICU (95% CI 0.99, 4.98, p=0.051). Conclusion: The prevalence of pre-eclampsia in this study is much lower than those quoted in other studies, whist clinical characteristics were almost similar